Advances in Non-equilibrium Statistical Mechanics: large deviations and long-range correlations, extreme value statistics, anomalous transport and long-range interactions - Lebowitz, Joel; Livi, Roberto; Majumdar, Satya; Mukamel, Davide; Ruffoli, Stefano; Casetti, Lapo; Lepri, Stefano (Il Colle di Galileo, 2015)
The workshop brought together leading researchers, young scientists and PhD students working in different areas of non-equilibrium statistical mechanics. The recent progress made in various fields of this broad discipline made the workshop timely and successful. Out-of-equilibrium systems are typically characterized by generic long-range correlations resulting in a variety of collective phenomena which are still awaiting an overall theoretical understanding. The main topics covered were: large deviations, current fluctuations, fluctuation relations, anomalous transport, statistics of extreme events and slow relaxation in non-equilibrium processes. The relation with equilibrium systems with long-range interactions, where ensembles become inequivalent, was also addressed. This workshop has strengthened the interaction among different communities and has led to the exploration of open problems and new research directions. Joint research in this field, combining theoretical investigations with an empirical component, has led to particularly fruitful exchanges.